Investigating perceptions of students receiving sports education towards eating habits and obesity - Kilic, Yakup; Yildirim, Eyyup (Birlesik Dunya Yenilik Arastirma ve Yayıncilik Merkezi, 2020)
This study aims to investigate perceptions towards eating habits and obesity in students receiving sports education in Turkey. The sample consisted of 360 randomly chosen students, who received sports education at Firat University, Agri Ibrahim Cecen University, Ardahan University and Mugla Sitki Kocman University. The sample was formed by adopting the convenience sampling method. For data collection, the ‘Three-factor eating questionnaire’ was used. The data were analysed for normality distribution in terms of the questionnaire and its subscales, which proved that the data provided a normality distribution. ‘Independent samples t-test’ was conducted to evaluate the level of differentiation in terms of the independent variables of gender and taking courses about nutrition and obesity. ‘One-way Variance Analysis’ was conducted to evaluate the level of differentiation in the variables of grade and the universities of the participants. The development level of the location where the students lived, income levels and cultural activities affected their eating. © 2020. United World Center of Research Innovation and Publication. All rights reserved.
Keywords: Eating habits; Education; Obesity; Sports; Students